Evaluating Environmental and Energy Performance Indicators of Food Systems, within Circular Economy and “Farm to Fork” Frameworks - Ghisellini, Patrizia; Ncube, Amos; Rotolo, Gloria Claudia; Vassillo, Chiara; Kaiser, Serena; Passaro, Renato; Ulgiati, Sergio (MDPI, 2023)
This study proposes a framework of environmental and energy performance indicators identified and critically evaluated within the scientific literature and the Agricultural European Database for the monitoring and evaluation of the Common Agricultural Policy of the European Union. The identified set of performance indicators encompasses the whole life cycle of agri-food systems from primary production stage until end-of-life stage in agreement with the circular economy and EU “farm to fork strategy” frameworks. In particular, the practices/goals/targets suggested in the latter (e.g., organic farming goals, more relevance assigned to plant-based diets, support for the creation of short supply chains, and reduction in food losses and waste) have guided the search for the main topics of interest in our analysis and the associated environmental and energy indicators. The results of this study evidence a proposed set of performance indicators selected from the literature among LCA and non-LCA indicators (midpoint LCA impacts, cumulative energy use, emergy accounting, and material flow accounting, among others) that could be helpful in integrating the EU CAP indicators for monitoring and evaluating efforts and achieved results toward implementing and controlling the effectiveness of the adopted “farm to fork” policy and related legislative measures, as well as the application of the circular economy model.